Disorder and defects in functional molecular frameworks - Cliffe, M; Matthew Cliffe (2015)
This Thesis explores the role of structural defects and disorder and their relationship to experimental data, with a particular emphasis on molecular framework materials. The question of how we can build atomistic models of amorphous materials from experimental data without needing to make system-specific assumptions is addressed. The role of 'structural invariance', i.e. the limited range of distinct local atomic environments within a material, as a restraint within reverse Monte Carlo refinement (RMC) is investigated. The operation of these invariance restraints operate is shown to be system-dependent and the challenges associated with effective refinement, e.g. configurational 'jamming', are also investigated. A generalisation to the 'structural simplicity', i.e. the simplest model, holding all else constant, is most likely to be correct. Three new metrics of structural simplicity are proposed: two intrinsically three-dimensional measures of local geometric invariance and one measure of local symmetry. These metrics are shown to robustly quantify the configurational quality. The ability of these metrics to act as effective restraints for the RMC refinement of amorphous materials is demonstrated by the construction of the first data-driven tetrahedral models of amorphous silicon. The role of defects and disorder within metal–organic frameworks (MOFs) is investigated through the canonical MOF UiO-66(Hf). Through a combination of techniques, including X-ray diffuse scattering, anomalous diffraction, total scattering and electron diffraction measurements, the existence of correlated metal-cluster absences in UiO-66(Hf) is demonstrated. Furthermore the ability to synthetically tune both the interactions and concentration of defects is shown. The thermomechanical properties of defective UiO-66(Hf) are also examined. UiO-66(Hf) is shown to rapidly densify by up to 5% (ΔV/V ) on ligand elimination. The resultant densified phase exhibits colossal (≥100MK-1) volumetric negative thermal expansion (NTE); the largest reported value for any MOF. Finally, the capability to tune the physical properties of MOFs through defect incorporation is demonstrated through the defect-dependence of both the densification and the NTE.